2020
DOI: 10.1371/journal.pone.0231462
|View full text |Cite
|
Sign up to set email alerts
|

Parent-child agreement in different domains of child behavior and health

Abstract: The present study aimed to investigate and compare parent-child agreement in different domains of child health and behavior. Methods Data were collected between 2011 and 2019 within the framework of the LIFE Child study (Germany). Different subgroups of 10-to 12-year-old children and their parents (n (max) = 692) completed questionnaires on several health behaviors (diet, media use, physical activity, sleep), parameters of health (behavioral strengths and difficulties, psychosomatic complaints), and school gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 57 publications
(109 reference statements)
2
25
4
Order By: Relevance
“…Being a girl increases the probability of parents’ overestimating children's HRQOL. In contrast to our results, other studies reported that the child’s gender did not significantly affect the parent–child agreement [ 45 47 ]. Waters, Stewart–Brown [ 48 ] reported that-parent-female child-dyads showed lower agreement than parent-boy dyads.…”
Section: Discussioncontrasting
confidence: 99%
“…Being a girl increases the probability of parents’ overestimating children's HRQOL. In contrast to our results, other studies reported that the child’s gender did not significantly affect the parent–child agreement [ 45 47 ]. Waters, Stewart–Brown [ 48 ] reported that-parent-female child-dyads showed lower agreement than parent-boy dyads.…”
Section: Discussioncontrasting
confidence: 99%
“…Visual inspection of the Bland-Altman plot also revealed that the agreement between child-parent dyads was stronger when the children had lower HRQoL scores, highlighting that parents have a good perception of children's well-being when it is impaired. In contrast with a previous study [35], our ndings suggest that the sex of the child may affect the degree of agreement between child and parent ratings. The differences between child and parent ratings indicate that it would be valuable to consider both parent and child ratings.…”
Section: Discussioncontrasting
confidence: 99%
“…Being a girl increases the probability of parents' overestimating children's HRQOL. In contrast to our results, other studies reported that the child's gender did not signi cantly affect the parent-child agreement (45)(46)(47). Waters, Stewart-Brown (48) reported that parents and a female child's dyads showed lower agreement than parent-boy dyads.…”
Section: Discussioncontrasting
confidence: 99%